Verità, natura e tecnica: servirsi, serbare, osservare - Visentin, Mauro (Bollettino Filosofico, 2023)
What we call “technology” is rooted in an original disposition of consciousness that consists in the ability to make use of something in view of something. To make use is a meaning that refers back to serve and to preserve. Both of the latter expressions have to do with the condition of the servant, that is, one who serves a master, who guards another's possession, who preserves on behalf of others. First and foremost, the purpose of technology is to preserve something that does not belong to us or belongs to us provisionally and which, therefore, we are at risk of losing. First of all, individual life. In this aspect it contrasts with nature, which preserves the collective life (of the species) through the succession of individual lives and, thus, by virtue of their mutual sacrifice. Technology does not address that possession that we are not at risk of losing i.e., the possession of truth. That which is a cause, has a purpose, is a means belongs to technology; truth is an object of contemplation. This means that truth does not serve (it is not the servant or handmaiden of anyone or anything) and that technology does not need truth, as it does not base its effectiveness on it. Keywords: Contemplation, Preserve, Serve, Technology, Truth